2015
DOI: 10.1111/1751-2980.12248
|View full text |Cite
|
Sign up to set email alerts
|

Prospective comparative study of inhibitory control test and psychometric hepatic encephalopathy score for diagnosis and prognosis of minimal hepatic encephalopathy in cirrhotic patients in the Indian subcontinent

Abstract: ICT is useful for diagnosing MHE in patients with cirrhosis. It is correlated with disease severity and predicts the development of OHE and probable survival with excellent test-retest reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 25 publications
3
37
0
2
Order By: Relevance
“…In the current study, the PHES and ICT did not correlate with the severity of liver disease, as measured by CTP score and MELD score. This observation matches results in the previous work done by Taneja et al 23 but opposed the findings of Gupta et al 22 who found correlation between ICT and severity of liver disease.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the current study, the PHES and ICT did not correlate with the severity of liver disease, as measured by CTP score and MELD score. This observation matches results in the previous work done by Taneja et al 23 but opposed the findings of Gupta et al 22 who found correlation between ICT and severity of liver disease.…”
Section: Discussionsupporting
confidence: 89%
“…The sensitivity of 78.87% and specificity of 66.06% with area under the curve of 0.724 (95% CI: 0.653-0.788) indicates that, in Indian patients, ICT has a much lower sensitivity, specificity, and area under the curve for MHE diagnosis. In one of the previous Indian studies, sensitivity, specificity and receiver operating characteristic of the ICT were 92.6%, 78.5% and 0.855 respectively, 22 while in another study they were 78%, 65.6% and 0.735 respectively for the diagnosis of MHE in liver cirrhosis. 23 For the diagnosis of MHE, the PHES is considered to be a reliable tool.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…In this study, only four subjects had OHE history, which would make the results difficult to interpret for the larger OHE Chinese population. Lastly, learning effects were observed in performing PHES . As a single‐visit study, we cannot draw conclusions on whether a learning effect will influence the result of EncephalApp Stroop Test.…”
Section: Discussionmentioning
confidence: 89%
“…The ICT is another test for diagnosis of MHE, and various studies have shown it to be important for prediction of overt HE. 16 The International Society for Hepatic Encephalopathy and Nitrogen Metabolism (ISHEN) recommends that two different tests should be used to diagnose MHE, which includes one of the tests, which is widely accepted to serve as the comparator. 17 The upcoming modalities for diagnosis of cognitive dysfunction in cirrhosis are biomarkers and newer imaging tools.…”
mentioning
confidence: 99%